On resolvent of the Levy process with matrix-exponential distribution of jumps - Karnaukh, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We consider the representations of resolvent for a Levy process whose jumps have a matrix-exponential distribution.